Konsep Negara Berbasis Hak sebagai Argumen Justifikasi Pengujian Konstitusionalitas Undang-undang - Kurnia, Titon Slamet (Jurnal Konstitusi, 2012)
This article argues that the concept of right-based State and right-based constitution are substantively the basis or justification for constitutional review of legislation or laws. The constitutionality of laws is determined by the idea that human rights are supreme or superior over the legislature and its legal product. Therefore, the legislature should respect human rights in law-making. This article also rejects the view that hierarchy of laws is the only basis for constitutional review of legislation or laws because this view only explains it formally. This argument cannot be applied to Britain or Israel which does not have a formal constitution.